Paradoksy komunikacji szkolnej – rozwazania na temat wybranych ograniczen rozwoju kompetencji komunikacyjnych uczniów we współczesnej szkole - Kuszak, Kinga (Kultura-Społeczeństwo-Edukacja, 2013)
The article points to the features of classroom communication which hinder the development of students’ communicative competences. The author describes the paradoxes of classroom communication re ected in the fact that the teachers enjoy signi cantly more rights and privileges than the students with regard to both the form and the content of the messages they express, as well as the paradoxes stemming from the arti cial, formalized language present in the classroom, which actually hinders the development of communicative skills.